Pedagogika jako nauka bez kompleksów = Pedagogy as a science without complexes - Śliwerski, Bogusław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Pedagogy is not unique among related social sciences, such as psychology or sociology, whose end (as a science) has already been announced many times, not only by a number of its representatives, but also by its opponents. Although the phenomena of scientific revolution and resulting paradigm changes have affected all areas of knowledge, including sciences, pedagogy is not going to disappear because it represents humanities and social sciences, and it is understood as the knowledge on education and training of a man.
Keywords: pedagogika